Technical Education and Skills Development Authority schools management in selected rural areas - Bilangel, Nina A. (2006)
A descriptive-comparative multiple-case study was undertaken to know how the managerial functions of planning, organizing, leading, and controlling are praticed in rural TESDA schools. The result showed that the cutting edge of TESDA schools was the ability to adapt to the needs of the industry and the community, and at the same time maintain a bureaucratic structure. This was made possible by a leader, who, with his political skill, was able to transform people through a higher level of motivation, which transcends personal goals in order to achieve the broader goals of TESDA. However, it was also seen that TESDA schools usually fail in the implementation of plans because of lack of control.